2021
DOI: 10.3390/ijerph182413264
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Equation Modeling of Mental Health Literacy in Healthcare Students

Abstract: Background: There is a high prevalence of mental illness among healthcare students, and most students with mental health problems are reluctant to seek help from mental health professionals. Help-seeking is a component of mental health literacy (MHL). Although MHL is conceptualized as multi-dimensional, a theory-based multi-construct of MHL is still lacking. We aimed to build a theory-based multi-construct of MHL to explore the pathways of help-seeking. Methods: The data were obtained from a survey on MHL amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 67 publications
0
11
1
Order By: Relevance
“…Also recognizing mental disorders is a very important predictor of HSBs by using MHSs. According to Lu et al (2021) recognizing mental illness had a positive direct effect on both help-seeking efficacy and maintenance of positive mental health of university students. Similarly, Pham et al (2020) confirmed the HSBs of university students by using MHSs when they had a mental breakdown, were worried or upset, and resourced to psychotherapy when they had psychological problems.…”
Section: Results Before the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Also recognizing mental disorders is a very important predictor of HSBs by using MHSs. According to Lu et al (2021) recognizing mental illness had a positive direct effect on both help-seeking efficacy and maintenance of positive mental health of university students. Similarly, Pham et al (2020) confirmed the HSBs of university students by using MHSs when they had a mental breakdown, were worried or upset, and resourced to psychotherapy when they had psychological problems.…”
Section: Results Before the Covid-19 Pandemicmentioning
confidence: 99%
“…These results have also been confirmed by Pham et al (2020) in their research. Recognizing a mental disorder is also a very important predictor of HSBs through using MHSs (Lu et al, 2021). Indeed, recognizing a mental illness has a positive direct effect on both help-seeking efficacy and maintenance of the positive mental health of university students.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this definition, Kutcher et al (2016) added an understanding of how to obtain and maintain good mental health to the conceptualization of MHL (Bjørnsen et al, 2017). Previous studies demonstrated that greater knowledge of maintaining good mental health was associated with increased positive help-seeking attitudes (Allouche et al, 2021; Lu et al, 2021). Educational programs or interventions for mental health promotion showed a positive relationship between the maintenance of positive mental health and help-seeking attitudes (Ashoorian et al, 2019; Hunt et al, 2019; E.…”
Section: Help-seeking Attitudementioning
confidence: 98%
“…Numerous empirical studies have examined the relationship between MHL and help-seeking attitudes (e.g., Allouche et al, 2021; H. C. Kim, 2021; Lu et al, 2021; Tomczyk et al, 2020). However, owing to the ongoing debate on what should be included in the construct of MHL (Spiker & Hammer, 2019; Wei et al, 2017), these studies may not fully capture the various components of MHL and have not yet reached reliable conclusions.…”
Section: Help-seeking Attitudementioning
confidence: 99%
See 1 more Smart Citation